2023
DOI: 10.3390/nu15020257
|View full text |Cite
|
Sign up to set email alerts
|

Waist Circumference Is an Essential Factor in Predicting Insulin Resistance and Early Detection of Metabolic Syndrome in Adults

Abstract: Background: Metabolic syndrome (Met-S) is considered one of the most important health problems of the 21st century. It includes a group of metabolic disorders that increase the risk of cardiovascular diseases such as overweight and obesity, elevated lipid profile and blood pressure and insulin resistance (IR). Based on the information mentioned above in which there seems to be a relationship between IR and Met-S, the objective of this work was twofold: on the one hand, to assess the relationship between the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Secondly, let’s continue the analysis based on population characteristics. Generally, older individuals, males, and abdominal obesity individuals tend to have poorer metabolic outcomes ( 50 52 ), and in the current study, we found that the proportion of MetS patients among these people was much higher ( Supplementary Table 2 ). Therefore, the higher risk of NAFLD associated with the ALT/HDL-C ratio in these populations may be mediated through other metabolic pathways that contribute to these unfavorable outcomes.…”
Section: Discussionsupporting
confidence: 54%
“…Secondly, let’s continue the analysis based on population characteristics. Generally, older individuals, males, and abdominal obesity individuals tend to have poorer metabolic outcomes ( 50 52 ), and in the current study, we found that the proportion of MetS patients among these people was much higher ( Supplementary Table 2 ). Therefore, the higher risk of NAFLD associated with the ALT/HDL-C ratio in these populations may be mediated through other metabolic pathways that contribute to these unfavorable outcomes.…”
Section: Discussionsupporting
confidence: 54%
“…Different studies have shown marked differences and guidelines for unification criteria in relation to the cutoff values and diagnosis performance for surrogate indices and variables that allow to predict IR, particularly those related to anthropometric measurement, and hormonal and biochemical parameters according to age, race, and ethnicity ( 20 , 52 , 58 61 ). Thus, although WC is gender and race/ethnicity specific, its use as a surrogate index for the determination of IR in population studies is limited because it may lead to the underestimation or overestimation of IR prediction; therefore, this index should be adjusted to height for a robust and universal use as a surrogate index for predicting IR ( 20 , 40 , 62 ). Similarly, it is important to highlight that BMI is age, gender, and race/ethnicity specific to predict IR, and countless cutoff values have been described in different population studies; therefore, this index should be carefully applied in personalized medicine rather than in population studies for predicting IR ( 44 , 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study involves a significant number of patients, but it is a very heterogeneous group-therefore, in order to verify the increased cardiovascular risk, we opted to categorize them into smaller groups based on age, gender, and nicotine addiction in accordance with the SCORE2 and SCORE2-OP tables. It is important to mention that we did not collect data on variables like insulin resistance (such as HOMA-IR), which could potentially impact the final findings (waist circumference is sometimes considered an indirect indicator of insulin resistance [33]). A significant drawback of this study is also the lack of additional anthropometric indicators, such as ABSI, Body Roundness Index, Conicity Index, WWI, BMI WC or others (which are known to be beneficial in assessing cardiovascular risk [22,[34][35][36])-nevertheless, this was done on purpose; the mentioned indicators are not typically used in regular clinical practice with patients who have overweight or obesity.…”
Section: Discussionmentioning
confidence: 99%